Influencer Authenticity: The Key to Triggering Impulsive Online Purchases - Rahadian, Dimas; Yolanda Masnita; Kurniawati; Anggi Puspita, Lintang (Universitas Indo Global Mandiri, 2025)
This study explored the influence of influencer marketing on online impulse buying intentions, focusing on the role of perceived authenticity as a mediating factor. With the rapid growth of social media and influencer marketing, the study aimed to understand how the congruence between consumers, influencers, and products can influence impulsive purchasing behaviors. Data were collected from 257 active Instagram users in the Jabodetabek region, using Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The findings showed that consumer-product congruence positively influenced online impulse buying intentions, with perceived authenticity significantly mediating this relationship. However, the congruence between consumers and influencers did not show a significant impact on impulse buying intentions. The study suggests that perceived authenticity is a key factor for companies to consider when choosing influencers, as it enhances consumer trust and impulsive purchasing behavior. Limitations of the study include the limited geographic focus on Jabodetabek and the single social media platform, Instagram. Future research should expand to other social media platforms and broader cultural contexts to further explore the role of authenticity in influencer marketing and its effects on impulsive buying. Keywords: Influencer Marketing, Perceived Authenticity, Online Impulse Buying Intentions